Antigenic characterization of different stocks of Trypanosoma, evansi by counter-immunoelectrophoresis - SINGH, VEER (The Indian Journal of Animal Sciences, 2013)
Counter-immimoelectrophoresis (CIE) was used for antigenic characterization of different stocks of Trypanosoma evansi The antigens were prepared from 7 different stocks from Hisar, Bareilly. Lucknow, Ludhiana, Bikaner and-Karnal of buffalo, equids and camel origins. These were maintained in albino rats after separating the trypanosomes. from blood through diethyl aminocthyl (DEAR) cellulose Be columns followed by sonication at 150 walls. The hyperimmune sera against each stock were raised in New Zealand White rahbits. Threeprecipitin lines were observed with each homologous antigen and antiserum. Variable precipitin lines numbering 2 to 5 were observed with heterologous antigens and antisera.